Africans: The History of A Continent - John Iliffe (USA Cambridge University Press, 1995)
This is a history of Africa from the origins of mankind right up to the South African general election of 1994. Africans have been pioneers struggling against disease and nature in an overwhelmingly hostile environment, and their social, economic and political institutions have been designed to ensure survival and maximise numbers. These institutions enabled them to survive the slave trade and colonial invasion, but in the context of medical progress and other twentieth-century innovations the same institutions have bred the most rapid population growth the world has ever seen. This demographic growth has lain behind the collapse of colonial rule, the disintegration of apartheid, and the instability of contemporary nations. Thus Iliffe depicts the history of the continent as a single story, binding today's Africans to the earliest human ancestors. --Publishers description.
The frontiersmen of mankind -- The emergence of food-producing communities -- The impact of metals -- Christianity and Islam -- Colonising society in western Africa -- Colonising society in eastern and southern Africa -- The Atlantic slave trade -- Regional diversity in the nineteenth century -- Colonial invasion -- Colonial change, 1918-1950 -- Independent Africa -- Industrialisation and race in South Africa.
Keywords: History, Geography and Archaeology (3GdJGQjN hGdLZQGajG hGdBKGQs; General